The Effect of Extended Education on Educational Quality and Inequality: An Event Study Approach - Ron Diris; Kim Fairley (Institute of Labor Economics (IZA), 2024)
This study examines the effect of extended education on school achievement and inequality in Dutch primary schools. We apply a panel event study design using rich longitudinal data on the use of extended education and school achievement in grades 1 through 6, to estimate the causal effect of extended education. The analysis reveals (precisely estimated) zero or low effects from the use of extended education. Interestingly, we identify a modest Ashenfelter dip right before the start of extended education, suggesting a reaction to an incidental poor school result. We explain the overall low effectiveness by the typical low-intensity use of extended education among Dutch primary school students, while we also identify high effectiveness for (a very small subset) of more intensive forms. We conclude that extended education has no meaningful implications for educational achievement or inequality in Dutch primary education.
Keywords: I21; I24; 330; education economics; extended education; tutoring; event study design